Стійкість синхронізованих та кластерних станів у системі зв'язаних кусково-лінійних відображень (Нелінійні коливання, 2004)
Parameter regions for different types of stability of synchronized and clustered states are obtainedfor two interacting ensembles of globally coupledone-dimensional piecewise linear maps. We analyze strong (asymptotic)and weak (Milnor) stability of the synchronized state, as well as itsinstability. We found that the stability and instability regions in the phase space depend only onparameters of the individual skew tent map, and do not depend on the ensembles size. In thesimplest non-trivial case of four coupled chaotic maps we obtain stabilityregions for coherent and two-cluster states. The regionsappear to be large enough to provide an effective control ofcoherent and clustered chaotic regimes. Transition from desynchronization tosynchronization is identified to be qualitatively different in smooth and piecewise linearmodels.